Improving patient flow in emergency department through dynamic priority queue - TAN, Kar Way (Institutional Knowledge at Singapore Management University, 2012)
Most queuing problems are based on FIFO, LIFO, or static priority queues; very few address dynamic priority queues. In this paper, we present a case in a hospital’s emergency department (ED) where the queuing process can be modeled as a time-varying M/M/s queue with re-entrant patients. In order to improve patient flow in the department, we propose the use of a dynamic priority queue to dispatch patients to consultation with doctors. We test our proposed model using simulation and our experimental results show that a dynamic priority queue is effective in reducing the length of stay (LOS) of patients and hence improving patient flow. Furthermore, we show that a hybrid scheme is effective in preventing starvation.